Minimizing Misconceptions: Designing an Electrical and Magnetic Syllabus for Prospective Elementary School Teachers Using Predict Observe Explain-Conceptual Change Text (POE-CCT) - Susanna Vonny Noviana Rante; Markus Deli Girik Allo (STAI Hubbulwathan Duri, 2024)
This study aims to 1) Obtain empirical data on the needs analysis for developing electrical and magnetic learning devices using the Predict-Observe-Explain (POE) approach assisted by Conceptual Change Text (CCT), and 2) Gather comprehensive information on designing a syllabus for electricity and magnetism using POE assisted by CCT. This qualitative research focuses on the define and design stages of the 4D model and involves 30 second-semester students from the Elementary School Teacher Education Study Program, including 6 men and 24 women, enrolled in the Basic Science Concepts course. Data collection methods included interviews to develop and validate a product based on needs analysis, such as graduate learning outcomes related to the course, relevant study materials, learning methods, time allocation, learning resources, references, learning media, and assessment criteria. The data was analyzed using content analysis techniques. The findings of this study confirm that 1) A learning tool using the POE-CCT approach is necessary to reduce misconceptions among prospective elementary school teachers, particularly in understanding the domains of electricity and magnetism, which are conceptually complex. The designed syllabus aims to address these misconceptions by incorporating POE learning tools assisted by CCT. This includes stages where students predict outcomes and reasons, observe and record their findings, and explain their observations followed by class discussions. 2) The syllabus development stage, based on needs analysis, results in POE learning tools with CCT assistance that promote independent prediction, observation, and explanation. This structured approach enhances active engagement, deeper understanding, and conceptual refinement through collaborative discourse, promising improved comprehension and retention of complex scientific concepts in the classroom.